2011
DOI: 10.1099/ijs.0.028753-0
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycetospora rishiriensis sp. nov., isolated from a lichen

Abstract: An actinomycete, strain RI109-Li102 T , was isolated from a lichen sample obtained from Rishiri Island in Japan. Cells of strain RI109-Li102T were Gram-positive, aerobic and non-motile and formed bud-like spore chains. The isolate grew with 0-3 % (w/v) NaCl, at pH 5-9 and at 10-30 6C (optimum 30 6C). The whole-cell hydrolysate contained meso-diaminopimelic acid, arabinose and galactose. The predominant menaquinone was MK-8(H 4 ) and the diagnostic phospholipids were phosphatidylethanolamine, phosphatidylcholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Recent studies have described the isolation of different species of actinomycete from lichen, such as Actinomycetospora iriomotensis (Yamamura et al, 2011a), Actinomycetospora rishiriensis (Yamamura et al, 2011b) and Nocardioides exalbidus (Li et al, 2007). In the course of our investigation into the diversity of actinomycetes in Thailand, we obtained strain LDG1-22 T from lichen Flavoparmelia sp.…”
mentioning
confidence: 99%
“…Recent studies have described the isolation of different species of actinomycete from lichen, such as Actinomycetospora iriomotensis (Yamamura et al, 2011a), Actinomycetospora rishiriensis (Yamamura et al, 2011b) and Nocardioides exalbidus (Li et al, 2007). In the course of our investigation into the diversity of actinomycetes in Thailand, we obtained strain LDG1-22 T from lichen Flavoparmelia sp.…”
mentioning
confidence: 99%
“…The 16S rRNA gene sequence similarities to members of the genus Actinomycetospora ranged from 97.0 to 98.4%. [8][9][10] The phylogenetic tree constructed with 16S rRNA gene sequence data of members of the genus Actinomycetospora and related genera using the neighbor-joining method showed that strain IR73-Li102 T formed a monophyletic clade with A. chiangmaiensis, A. corticola and A. rishiriensis (Figure 1). Moreover, this clade was strongly supported by the maximum-likelihood and maximum parsimony trees with high bootstrap values.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, several rare actinomycetes were isolated from lichen samples collected in Japan, and were proposed as new taxa, named Nocardioides exalbidus, Leifsonia lichenia, and Actinomycetospora rishiriensis. [6][7][8] The genus Actinomycetospora was originally proposed by Jiang et al 9 as a member of the family Pseudonocardiaceae, and was later amended by Tamura et al 10 At the time of writing, nine Actinomycetospora species have been characterized by polyphasic taxonomic approaches. The type strain of the genus Actinomycetospora, A. chiangmaiensis, was originally isolated from a soil sample in northern Thailand, whereas the other species were from soil, tree bark, and lichen samples collected in Japan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] During the screening of lichen-associated actinobacteria, we isolated a novel actinobacterium (strain RI148-Li105 T ) from a foliaceous lichen sample collected from Rishiri Island, Hokkaido, Japan. Comparative 16S rRNA gene sequence analysis revealed that the isolate is related to the genus Luteimicrobium.…”
Section: Introductionmentioning
confidence: 99%